PENGARUH PEMBELAJARAN DARING DENGAN APLIKASI QUIZIZZ TERHADAP MOTIVASI DAN HASIL BELAJAR DI SMA NEGERI 3 SUNGAI KAKAP - Purwanti, Ajeng; Achmadi, Achmadi; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this study to analyze Effect of Online Learning Application on Students Motivation and Learning Outcomes in Economics Subject Class XI IPS SMA Negeri 3 Sungai Kakap. The method used quantitative research in the form of ex post facto research. Sources of data in this study obtained by questionnaires and documentation. The results of this study indicate that online learning activities using the quizizz application are quite active with an active percentage of 37.36%. Students learning motivation with online learning is also quite active with a percentage of 36.98%. As for the effect of online learning on learning outcomes, there is an influence of online learning activities on student learning outcomes with the results of the regression calculation Freg Ftable = 2.01 1.5343 so that Ho is"¦ rejected and Ha is accepted. Furthermore, the influence of learning motivation on student learning outcomes is categorized quite significant, where from the calculation of the regression Freg Ftable = 4.74 2.20 where Ho is rejected and Ha is accepted. Based on the results of the study, it can be concluded"¦ that online learning has an effect on students' motivation and learning outcomes